Telehealth and COVID-19: Empowering Standards of Management for Patients Affected by Phenylketonuria and Hyperphenylalaninemia - Valentina Rovelli (MDPI AG, 2021)
Phenylketonuria (PKU) and Hyperphenylalaninemia (HPA) are inborn errors of metabolism (IEM) due to mutations in the PAH gene resulting in increased blood phenylalanine (Phe) concentrations. Depending on the Phe levels, a lifelong dietary intervention may be needed. During the COVID-19 pandemic, finding new strategies to ensure follow-up and metabolic control for such patients became mandatory and telehealth was identified as the most eligible tool to provide care and assistance beyond barriers. The aim of this study was to evaluate how telehealth use may have impacted disease follow-ups. Seven hundred and fifty-five patients affected by PKU/HPA in follow-ups at the Clinical Department of Pediatrics (San Paolo Hospital, ASST Santi Paolo e Carlo, University of Milan, Italy) were included in this study. The data regarding the used telehealth model, type of performed consultations and patients’ perspectives were retrospectively collected and analyzed after a one-year experience of implemented follow-ups. The results demonstrated that telehealth seemed to be a useful tool to improve the adherence to treatment and that it could guarantee continuous assistance and care beyond the surrounding epidemiological status. Patients expressed great satisfaction with the offered services and requested that they were implemented in standards of care on a long-term basis. Our results suggested the implementation of telehealth in the management guidelines for PKU/HPA patients.